2000
DOI: 10.1164/ajrccm.161.1.9802048
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Airways Inflammation and Asthma Severity

Abstract: In order to investigate the relationship between airways inflammation and disease severity, and improve the understanding of persistent asthma, 74 asthmatics, with disease severity ranging from intermittent, to mild to moderate and severe persistent (classified according to the Global Initiative for Asthma [GINA] guidelines), and 22 nonatopic control subjects were studied using the method of induced sputum. Sputum was analyzed for total and differential cell counts concentrations of albumin, and levels of eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
337
4
19

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 528 publications
(380 citation statements)
references
References 39 publications
16
337
4
19
Order By: Relevance
“…These phenotypes, including allergic asthma, severe steroid-resistant asthma, asthma associated with obesity, induced by exercise, exposure to air pollutants or to aspirin, are characterized by different cellular networks supporting the chronic inflammation. The role of Th2 lymphocytes and eosinophils infiltrating the lung in the pathogenesis of the allergic form of the disease is supported by several evidences (3), and more recently, it has been suggested that Th17 lymphocytes and neutrophils could be involved in nonatopic (70) and in steroid-resistant (87) asthma. The definition of different asthma phenotypes is crucial for redirecting the therapeutic approach, which in future will be hopefully personalized for each patient.…”
Section: Possible Future Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…These phenotypes, including allergic asthma, severe steroid-resistant asthma, asthma associated with obesity, induced by exercise, exposure to air pollutants or to aspirin, are characterized by different cellular networks supporting the chronic inflammation. The role of Th2 lymphocytes and eosinophils infiltrating the lung in the pathogenesis of the allergic form of the disease is supported by several evidences (3), and more recently, it has been suggested that Th17 lymphocytes and neutrophils could be involved in nonatopic (70) and in steroid-resistant (87) asthma. The definition of different asthma phenotypes is crucial for redirecting the therapeutic approach, which in future will be hopefully personalized for each patient.…”
Section: Possible Future Applicationsmentioning
confidence: 97%
“…In those patients with asthma in which inflammation is nonatopic, non-IgE-dependent, and noneosinophilic, airway neutrophilia is correlated with asthma severity, suggesting a major role for neutrophils, at least in this subset of patients with asthma (70,71). Neutrophilic inflammation has also been described in sudden-onset fatal asthma and neutrophil numbers are highly elevated in status asthmaticus (72), thus suggesting a possible role for these cells in severe and fatal asthma.…”
Section: Th17 Lymphocytes and Asthmamentioning
confidence: 99%
“…In humans, no significant correlation was found between the degree of airway responsiveness and sputum inflammatory cells, which are two major features of asthma [4][5][6]. Concurrently, different strains of mice exhibit various degrees of airway responsiveness and inflammation despite identical sensitization and airway challenge with an allergen [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated eosinophil counts in blood and sputum is associated with disease severity [13,14]. As early as 1975, Horn et al [15] observed that increased blood eosinophil counts correlate with increasing airway obstruction in patients undergoing a pulmonary function test.…”
Section: Introductionmentioning
confidence: 99%